Genitourinary Problems of Female Orphan Adolescents: Genitourinary problems (Journal of Preventive and Social Medicine, 2020)
Introduction: Genitourinary problems are major health problems affecting millions of people each year, especially among female adolescents. This problem often associated with significant morbidity and mortality.Objective: The study aimed to find out genitourinary problems of female orphan adolescents.Methodology: A cross sectional study was conducted from January to December 2017, among 308 female orphan adolescents, which was selected purposively. Data were collected by face to face interviewing by using pretesting questionnaire and checklist which covers demographic characteristics, genital and urinary problems along with menstrual hygiene practices. Data were analyzed by using SPSS 20.0 version.Results: The study found that mean± SD age of the respondent 11.89 ± .749 years, 62% has menstrual problems followed by 37.6% has painful menstruation, 17.4% has irregular menstrual cycle, 13.1% has headache/vertigo, 11.4% had generalized body ache/leg cramps, 7.4% has polymenorrhea , 4.8% has menorrhagia, 2.8% has oligomenorrhea and 23% has foul smelling vaginal discharge. There is an association between age group of the respondents and their pattern of menstrual cycle (p=0.005), association between foul smelling vaginal discharge and itching of the respondents (p=0.000), association between menstrual hygiene and ways of drying of used cloth, multivariate analysis shows the association between menstrual hygiene and perennial cleaning (p= 0.797), taking bath (p=0.000) and ways of drying of used cloth (0.029) during menstruation. And 40.9% has urinary problems followed by 33.6% has painful micturition, 28.3% has burning sensation during micturition and 4.1% has incomplete voiding of urine.Conclusion: The study concluded that significant number of respondents suffer from one or more genitourinary problems. Educational level does not comply the knowledge of these adolescents regarding menarche. Many of them are still used to use old cloth during menstruation. Study recommended the prevention of genitourinary problems by improving knowledge of genitourinary tract physiology, reasons, complication, drinking plenty of water, emptying bladder completely as soon as feel the urge and maintain proper perennial hygiene with changing absorbent frequently during menstruation.JOPSOM 2019; 38(2): 9-14